2016
DOI: 10.1002/brb3.504
|View full text |Cite
|
Sign up to set email alerts
|

Organizational topology of brain and its relationship to ADHD in adolescents with d‐transposition of the great arteries

Abstract: ObjectiveLittle is currently known about the impact of congenital heart disease (CHD) on the organization of large‐scale brain networks in relation to neurobehavioral outcome. We investigated whether CHD might impact ADHD symptoms via changes in brain structural network topology in a cohort of adolescents with d‐transposition of the great arteries (d‐TGA) repaired with the arterial switch operation in early infancy and referent subjects. We also explored whether these effects might be modified by apolipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 41 publications
(95 reference statements)
2
46
0
1
Order By: Relevance
“…Increased small‐worldness was associated with lower intelligence and poorer reading, math, and executive function . Finally, increased cost and transitivity were associated with hyperactivity and impaired attention …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Increased small‐worldness was associated with lower intelligence and poorer reading, math, and executive function . Finally, increased cost and transitivity were associated with hyperactivity and impaired attention …”
Section: Resultsmentioning
confidence: 94%
“…Among these eight studies, six also had a larger proportion of males in the group with CHD than in the comparison group. In addition, ages between the CHD and comparison groups were significantly different in seven studies: in two, those with CHD were younger than comparison individuals; in five they were older. Exploratory analyses were conducted in seven studies, thus presenting a risk of bias due to possible selective reporting of the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been no reported structural or functional network‐based studies on the fetal or neonatal brain in CHD. However, in adolescents who had undergone repair of TGA in infancy, disrupted structural network organization was associated with a higher risk of attention deficit disorder and cognitive dysfunction . Both adolescents and adults who underwent surgery for CHD displayed altered functional activity during working memory tests compared with controls .…”
Section: Brain Network Analysis and Functional Outcomes In Adolescentmentioning
confidence: 96%
“…Diminished white matter microstructure may contribute to cognitive compromise in adolescents who underwent open-heart surgery in infancy. Recently, special brain MRI investigations have suggested that disorganization of neuronal networks may contribute to increased attention deficiency hyperactivity disease symptoms in adolescents with TGA (56). …”
Section: Encephalopathy Of Chd: Delayed Maturation Injury and Neuromentioning
confidence: 99%